Exploring the Impact of Mindfulness on Academic Performance: A Qualitative Study on Tertiary Institution Students, using In-depth Interviews - Kayiranga, Keza (The IIE, 2020)
It has been noted that many students suffer from anxiety when facing difficult academic tasks (Dobson, 2012). High levels of anxiety therefore tend to alter the student’s psychological functioning to the extent that memory, attention, and concentration are affected (Franco, Manâs, Cangas & Gallego, 2010). Mindfulness training has been demonstrated to lessen the negative effects of anxiety on physical and psychological health, significantly reducing anxiety (Franco et al., 2010). Mindfulness has also been efficient in aiding the reduction of test anxiety amongst students (Altairi, 2014). The present study therefore aimed to explore whether Mindfulness has had an impact on the academic performance university students, particularly those who practice it. The study was designed as a qualitative study. Data for this study was collected through the usage of semi-structured interviews where each participants where asked a set of open-ended questions that enabled the researcher to gain an in-depth understanding on the topic. Findings from study suggests that mindfulness practice has been efficient in aiding the targeted students focus more, avoid self-judgement that leads to anxiety and obtain better time management skills. All participants believed they have seen improvement in their academic performance due to being in a better and calmer mental state, learning to organise themselves better and in essence doing their work early and gradually, avoiding to put pressure on themselves.
Keywords: Mindfulness; Academic performance; Tertiary institutions; Students